Choroidal Thickness in Eyes with Band Atrophy of the Optic Nerve from Chiasmal Compression - Luiz Guilherme Marchesi Mello; Ana Claudia F. Suzuki; Giuliana Rovito de Mello; Rony Carlos Preti; Leandro C. Zacharias; Mário L. R. Monteiro (Journal of Ophthalmology)
Background. The choroid is a vascular tissue that helps maintain retinal and prelaminar optic nerve head function. Choroidal thickness has been previously studied in diseases accompanied by retinal neural loss, but the relationship between the two sets of measurements is not clear. In eyes with temporal hemianopia as a result of chiasmal compression lesions (CCL), retinal neural loss tends to be greater in the nasal than the temporal hemiretina, a fact that may be useful in evaluating the effect of inner retinal layer loss on choroidal thickness. Purpose. To evaluate macular and peripapillary choroidal thickness on swept-source optical coherence tomography (SS-OCT) in eyes with temporal hemianopia as a result of chiasmal compression and in healthy controls. Methods. 33 eyes of 26 patients with band atrophy of the optic nerve and temporal visual field defects as a result of previously treated suprasellar tumors (CCL group) and 40 eyes of 21 healthy controls underwent SS-OCT scanning. The thickness of the peripapillary retinal nerve fiber layer (pRNFL), the peripapillary choroid (pChoroid), the macular RNFL (mRNFL), the macular ganglion cell layer (mGCL), and the macular choroid (mChoroid) was expressed globally and by sector (peripapillary quadrants and macular hemifield and quadrants). Ratios between macular nasal and temporal hemifield and quadrantic measurements were calculated using generalized estimated equation models, and the two groups were compared. Results. The pRNFL, mRNFL, and mGCC thicknesses were significantly smaller in the CCL group than in the control group (64.67 ± 10.53 μm, 29.68 ± 5.80 μm, and 80.60 ± 10.17 μm vs. 103.78 ± 12.23 μm, 39.89 ± 3.82 μm, and 105.51 ± 7.76 μm, respectively; p<0.001). For the choroid, the only difference between the groups was increased macular nasal hemifield and superonasal quadrant thickness in CCL (222.47 ± 61.05 μm and 230.45 ± 58.59 μm in the CCL group, respectively vs. 190.68 ± 52.54 μm and 197.65 ± 54.80 μm in the control group, respectively; p<0.05). The temporal/nasal ratios were significantly higher for the mRNFL and mGCC parameters and significantly lower for the mChoroid parameters in the CCL group, except for the superotemporal/superonasal quadrant ratio. Conclusions. The choroid does not thin after the inner retinal layer becomes damaged due to CCL and may even be thicker in some areas with corresponding severe retinal neural loss. While further studies are needed to interpret these findings, choroidal thinning is most likely not secondary to optic nerve disease-related inner retinal neural loss.